PREVALENCE DE LA POLYKYSTOSE RENALE AUTOSOMIQUE DOMINANTE (PKRAD) Au niveau du centre d’hémodialyse de l’hôpital SEHAIRI Kamal Laghouat - TAOUSSI Imane; HAMZA Hafsa (université ammar telidji laghouat, 2025)
Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disorder, characterized by the progressive development of bilateral renal cysts, often associated with extrarenal manifestations, primarily hepatic. It is a major cause of end-stage renal disease, highlighting the need for early diagnosis and management. This study involved a series of 28 patients diagnosed with ADPKD, aiming to analyze its prevalence, clinical and paraclinical features, as well as progression to chronic hemodialysis. The majority of patients were female (53.6%), with a predominance of adults aged 36 to 59 years. The most frequent mode of discovery was family or incidental screening, followed by lumbar pain and hypertension. The most common comorbidity was hypertension (46.4%), followed by diabetes and heart failure to a lesser extent. About 50% of patients had associated hepatic involvement, and one-third progressed to chronic hemodialysis, most after more than ten years of disease evolution. Kidney transplantation was infrequent in this cohort (14.3%). These findings highlight the importance of family screening, regular nephrological follow-up, and comprehensive management including cardiovascular risk factors. The observed prevalence of ADPKD in this population underlines the need for greater awareness among healthcare professionals and structured long-term care. Keywords: autosomal dominant polycystic kidney disease, end-stage renal disease, family screening, arterial hypertension, comorbidities, chronic hemodialysis, kidney transplantation, hepatic involvement, nephrological follow-up, hereditary diseases
CD-ROM